Standardized Physician-Administered Patient-Centered Discharge Protocol Improves Patients' Comprehension. Issue 5 (May 2017) - Caceres, Jennifer W.; Alter, Scott M.; Shih, Richard D.; Fernandez, Jimmy D.; Williams, Frederick K.; Paley, Richard; Benda, William; Clayton, Lisa M.
Abstract : Objectives: Patients are 30% less likely to be readmitted or visit the emergency department if they have a clear understanding of their discharge instructions. A standardized approach to a hospital discharge plan has not been universally implemented, however. Our goal was to increase patients' comprehension of discharge instructions by implementing a standardized patient-centered discharge planning protocol that uses a physician team member to explain these plans. Methods: This was a prospective study that included all of the patients discharged from an inpatient medical teaching service in a community-based hospital during the study period. We used two 4-week periods separated by 4 months in which training and practice with the study intervention took place. Patients' understanding of discharge instructions was assessed via a follow-up telephone call from a physician co-investigator within 1 week of each patient's discharge. Differences in patients' understanding between groups were analyzed. Results: A total of 181 patients were enrolled, with 9 lost to follow-up. After implementation of the discharge planning protocol, a statistically significant improvement in patients' understanding was found in study subjects' knowledge of their diagnosis, the adverse effects of their medications, whom to call after discharge, and follow-up appointments. Conclusions: Institution of a standardized patient-centered discharge planning protocol can improve patients' understanding of several key components of their discharge process, which may lead to improved compliance with instructions and outcomes. Abstract : Supplemental digital content is available in the text.